When to punish is not to discipline - Antillano, Andrés (Carceral communities in Latin America, 2021)
Based on our ethnographic work in a Venezuelan prison, we discuss how state power withdraws from the carceral space, which fosters the emergence of forms of inmate self-rule. The state’s abdication of its traditional disciplinary role constitutes a displacement of a prison order produced “from above,” to one produced “from below” by incarcerated subjects themselves. Those shifts in carceral functioning, a consequence of mass imprisonment and the eroded capacity to regulate the interned life, point to a mutation in the prison’s social position. No longer does the prison seek to discipline, treat, or normalize the poor. On the contrary, the prison concentrates, reproduces, and reinforces the exclusion of a surplus population. In this context, the prison duplicates social exclusion through institutional abandonment.